EU responses to the ‘refugee’ crisis - Ribeiro, I. M. (Summer School Border Crossings: European and North American responses to the current migration crisis, 2019)
The goal of this lecture is to explore how the European Union's (EU) crisis management actorness has evolved since the creation of the European Security and Defence Policy (E/CSDP) in the late 1990s, in order to contribute to the understanding of the recent phenomenon of securitization of humanitarian aid and development policies at the EU level. The EU’s institutional discourse has evolved from assuming responsibility for managing others’ crises to making others accountable and capable to deal with their own crises (especially in the neighbourhood area), in order to ensure its own (European) physical and ontological security. Despite an apparent decrease in the EU’s security actorness and normative ambitions, its refocus towards capacity building and development lead to the consolidation of a security-development nexus, which does not mean a decrease in the EU’s normative ambitions, but simply a refocus thereof.